Advancing Patient Advocacy in Mycology: Cultivating Collaboration in Education, Research, and Policy - Rob Purdie; Rasha Kuran; Ana Alastruey-Izquierdo; Hatim Sati; Juan Luis Rodriguez-Tudela; Martin Hoenigl; John Perfect; Rita Oladele; Thomas J. Walsh; Tom Chiller (Mycopathologia, 2025)
In the healthcare landscape, diseases such as cancer and HIV/AIDS have benefited from the patient's perspective. For fungal diseases, the patient voice remains absent in critical areas such as policy formulation, funding decisions, and research priorities. Patients affected by fungal disease, along with their caregivers and advocacy groups, possess invaluable insights into the challenges and unmet needs they face. By elevating their voices and experiences, policymakers, funding agencies, and researchers can gain a more comprehensive understanding of the multifaceted nature of fungal disease and the urgency of addressing them. This paper addresses the pressing need for a coordinated effort to elevate the patient voice in advocating for improved policies, increased funding, and enhanced research initiatives regarding fungal disease.

Correction: Push-pull tests for estimating effective porosity: expanded analytical solution and in situ application - Charles J. Paradis; Larry D. McKay; Edmund Perfect; Jonathan D. Istok; Terry C. Hazen (Hydrogeology Journal, 2019)

Push-pull tests for estimating effective porosity: expanded analytical solution and in situ application - Charles J. Paradis; Larry D. McKay; Edmund Perfect; Jonathan D. Istok; Terry C. Hazen (Hydrogeology Journal, 2018)
The analytical solution describing the one-dimensional displacement of the center of mass of a tracer during an injection, drift, and extraction test (push-pull test) was expanded to account for displacement during the injection phase. The solution was expanded to improve the in situ estimation of effective porosity. The truncated equation assumed displacement during the injection phase was negligible, which may theoretically lead to an underestimation of the true value of effective porosity. To experimentally compare the expanded and truncated equations, single-well push-pull tests were conducted across six test wells located in a shallow, unconfined aquifer comprised of unconsolidated and heterogeneous silty and clayey fill materials. The push-pull tests were conducted by injection of bromide tracer, followed by a non-pumping period, and subsequent extraction of groundwater. The values of effective porosity from the expanded equation (0.6–5.0%) were substantially greater than from the truncated equation (0.1–1.3%). The expanded and truncated equations were compared to data from previous push-pull studies in the literature and demonstrated that displacement during the injection phase may or may not be negligible, depending on the aquifer properties and the push-pull test parameters. The results presented here also demonstrated the spatial variability of effective porosity within a relatively small study site can be substantial, and the error-propagated uncertainty of effective porosity can be mitigated to a reasonable level (< ± 0.5%). The tests presented here are also the first that the authors are aware of that estimate, in situ, the effective porosity of fine-grained fill material.

Spontaneous imbibition of water and determination of effective contact angles in the Eagle Ford Shale Formation using neutron imaging - Victoria H. DiStefano; Michael C. Cheshire; Joanna McFarlane; Lindsay M. Kolbus; Richard E. Hale; Edmund Perfect; Hassina Z. Bilheux; Louis J. Santodonato; Daniel S. Hussey; David L. Jacobson; Jacob M. LaManna; Philip R. Bingham; et al. (Journal of Earth Science, 2017)

The RIG-I-like helicase receptor MDA5 (IFIH1) is involved in the host defense against Candida infections - M. Jaeger; R. van der Lee; S.-C. Cheng; M. D. Johnson; V. Kumar; A. Ng; T. S. Plantinga; S. P. Smeekens; M. Oosting; X. Wang; W. Barchet; K. Fitzgerald; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Autophagy is redundant for the host defense against systemic Candida albicans infections - S. P. Smeekens; R. K. Malireddi; T. S. Plantinga; K. Buffen; M. Oosting; L. A. B. Joosten; B. J. Kullberg; J. R. Perfect; W. K. Scott; F. L. van de Veerdonk; R. J. Xavier; E. van de Vosse; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Evaluation of a digital microfluidic real-time PCR platform to detect DNA of Candida albicans in blood - W. A. Schell; J. L. Benton; P. B. Smith; M. Poore; J. L. Rouse; D. J. Boles; M. D. Johnson; B. D. Alexander; V. K. Pamula; A. E. Eckhardt; M. G. Pollack; D. K. Benjamin; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

A Chronological History of the International Conference on Cryptococcus and Cryptococcosis (ICCC), an Invaluable Forum for Growth of the Cryptococcal Research Field and Clinical Practice - Kyung J. Kwon-Chung; John R. Perfect; Stuart M. Levitz (Mycopathologia, 2012)

The impact of caspase-12 on susceptibility to candidemia - D. C. Rosentul; T. S. Plantinga; W. K. Scott; B. D. Alexander; N. M. D. van de Geer; J. R. Perfect; B. J. Kullberg; M. D. Johnson; M. G. Netea (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Pulmonary cryptococcosis in patients without HIV infection: factors associated with disseminated disease - J. W. Baddley; J. R. Perfect; R. A. Oster; R. A. Larsen; G. A. Pankey; H. Henderson; D. W. Haas; C. A. Kauffman; R. Patel; A. K. Zaas; P. G. Pappas (European Journal of Clinical Microbiology & Infectious Diseases, 2008)

Zygomycosis: the re-emerging fungal infection - M. Chayakulkeeree; M. A. Ghannoum; J. R. Perfect (European Journal of Clinical Microbiology & Infectious Diseases, 2006)

Global Distribution and Outcomes for Candida Species Causing Invasive Candidiasis: Results from an International Randomized Double-Blind Study of Caspofungin Versus Amphotericin B for the Treatment of Invasive Candidiasis - A. L. Colombo; J. Perfect; M. DiNubile; K. Bartizal; M. Motyl; P. Hicks; R. Lupinacci; C. Sable; N. Kartsonis (European Journal of Clinical Microbiology & Infectious Diseases, 2003)

Surface characteristics of necrotrophic secondary hyphae produced by the bean anthracnose fungus, Colletotrichum lindemuthianum - Sarah E. Perfect; Jonathan R. Green; Richard J. O'Connell (European Journal of Plant Pathology, 2001)